Feasibility Analysis of Station Construction Project Public Refueling (Petrol Station) - Joharudin Joharudin; Wildan Madhani Al Rosyid; Oki Purnama; Sulistijo Edhy Purnomo (Journal of World Science, 2025)
The development of fuel infrastructure in remote areas remains a critical challenge for Indonesia's energy access equity, particularly in regions with limited petrol station coverage relative to population density and vehicle growth. This study aims to analyze the financial feasibility of the construction of petrol stations in Terjun Jaya Village, Betara District, West Tanjung Jabung Regency. The method used is a project feasibility study with a quantitative descriptive approach. The analysis includes aspects of investment costs, revenue projections, and financial indicators such as Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), Break Even Point (BEP), and Profitability Index (PI). The results of the study show that this petrol station project is financially feasible with a Net Present Value of IDR 7,155,058,232, an Internal Rate of Return of 11.24%, a Payback Period of 4 years and 1 month, and a Profitability Index of 1.62%. The project shows robust market potential supported by regional vehicle population data indicating 176,435 total vehicles in the area requiring regular fuel access. The implications suggest that strategic petrol station development in underserved rural areas can achieve both financial sustainability and significant social impact by improving energy access equity while generating attractive returns for investors.